Can 18F-FDG PET/CT Metabolic Tumor Volume Contribute to Better Prognostication in Pediatric Hodgkin's Lymphoma? - Ramdas, Sangeetha; Sunny, Saumya Sara; Srinivasan, Hema Nalapalu; John, Rikki Rorima; Kompithra, Rajeev Zachariah; Gowri, Mahasampath; Joseph, Leenu Lizbeth; Hepzibah, Julie; Mathew, Leni Grace (Indian Journal of Medical and Paediatric Oncology, 2025)
Studies in adults have shown that metabolic tumor volume (MTV) in fluorine-18 fluorodeoxyglucose (18F-FDG) positron emission tomography (PET)/computed tomography (CT) is a strong predictor of event-free survival (EFS) and overall survival (OS) in Hodgkin's lymphoma, often outperforming clinical scores and molecular predictors. However, there very few studies on pediatric Hodgkin's lymphoma (PHL), with conflicting results.This retrospective study was conducted to evaluate the feasibility of MTV assessment in PHL and to assess its prognostic role, given the paucity of data from the developing world and the technical expertise required.Children with PHL, treated per EuroNet-PHL-C1 interim guidelines/C2 protocol at our center from 2017 to 2020 who had baseline and interim PET (iPET) scan done at our institution were included. MTV was measured in tumor areas with standardized uptake value (SUVmax) ≥2.5. MTV and SUVmax were compared at diagnosis and after two chemotherapy courses.Sixty-one children (male:female = 1.5:1; mean age: 10.10 years) were recruited and categorized into four stages (SI: 11; SII: 15; SIII: 21; and SIV: 14) and three treatment groups (TG1: 16; TG2: 11; and TG3: 34). Based on iPET, 47 and 14 children were adequate and inadequate responders, respectively. At a median follow-up period of 54 months, the OS was 96.7% and the EFS was 85.2%. The median SUVmax and MTV were both found to increase with advancing disease stage with a positive correlation (r = 0.41; p = 0.002). The difference in the median MTV was statistically significant for SII versus SIII (p = 0.004) but not for the median SUVmax (p = 0.13). Similarly, the difference in the median MTV was statistically significant for TG2 versus TG3 (p = 0.001) but not for the median SUVmax (p = 0.06). The median MTV in baseline PET/CT with Deauville score–based treatment response groups for adequate and inadequate responders was 98.35 (37.93–298.2) mL and 145 (84.43–463.5) mL, respectively (p = 0.31), and for those with events versus no events, the median MTV was 304 (30.45–452.7) mL and 105.35 (37.9–309.2) mL, respectively (p = 0.82).Baseline PET/CT MTV showed better correlation than SUVmax in delineating stage and treatment groups. However, MTV in isolation was not sensitive or specific enough in prognosticating treatment response or EFS (relapse or death) in this study setting. The addition of significant clinico-biochemical parameters with MTV for future studies could enhance prognostication.
Keywords: 18F-FDG PET/CT; event-free survival; metabolic tumor volume; overall survival; pediatric Hodgkin's lymphoma; prognostication; standardized uptake value